Engaging the Arts for Wellbeing in the United States of America: A Scoping Review - Pesata, Virginia; Colverson, Aaron; Sonke, Jill; Morgan-Daniel, Jane; Schaefer, Nancy; Sams, Kelley; Carrion, Flor Maria-Enid; Hanson, Sarah (Frontiers in Psychology, 2022)
There is increasing interest today in how the arts contribute to individual and community well-being. This scoping review identified and examined ways in which the arts have been used to address well-being in communities in the United States. The review examined 44 publications, with combined study populations representing a total of 5,080 research participants, including marginalized populations. It identified the types of artistic practices and interventions being conducted, research methods, and outcomes measured. It highlights positive associations found across a broad spectrum of psychological, physical, and social outcomes, including improvements in self-esteem and identity formation, cognition, physical balance, and physical conditioning. It also reports negative outcomes of arts interventions that may be underreported. The study identifies the need for core outcomes sets and reporting guidelines for advancing evidence synthesis in this area.